THE INFLUENCE OF KAMPUS MENGAJAR MBKM PROGRAM TO ENHANCING STUDENTS' SOCIAL COMPETENCE - Kusumo Hadi Santoso; Dyah Kurniawati (Universitas PGRI Ronggolawe Tuban, 2024)
In Society 5.0, Indonesia adapts education for critical thinking and innovation. Learning emphasizes life skills and collaboration for skilled human resources. Global competencies like communication and critical thinking are crucial. Social comppetence are vital for succes. Approaches like music therapy and democratic classrooms contribute, while MBKM, aligned with independent learning, enhances social competence through collaborative Teaching Campus activities.This quantitative study at Unirow examines the impact of Teaching Campus activities within the Merdeka Learning Campus program on students'' social competence that consist of 10 students were divided into two groups. A specially designed social competence scale assessed communication, collaboration, problem-solving, and patriotism. Descriptive statistics and t-test analysis compared social competence differences between participating and non-participating students.The study examines the impact of the Teaching Campus program on students'' social competence, comparing participants and non-participants. Demographic data reveals diversity in the participating group. The analysis indicates a significant positive influence on social competence, emphasizing the program''s role in fostering communication, collaboration, and problem-solving skills. Teacher-student relationships and family patterns are also highlighted as crucial factors in social competence development.The study affirms the significant impact of the Campus Teaching program on students'' social competence, crucial for Society 5.0 and academic success. The findings provide a valuable basis for future research and policy initiatives. Caution is advised in generalizing the results beyond the specific context of English Language Education at Universitas PGRI Ronggolawe Tuban.